Disrespect and abuse during labour and birth amongst 12,239 women in the Netherlands: a national survey - Marit S. G. van der Pijl; Corine J. M. Verhoeven; Rachel Verweij; Tineke van der Linden; Elselijn Kingma; Martine H. Hollander; Ank de Jonge (BMC, 2022)
Plain language summary Disrespect and abuse during labour and birth is a globally recognized phenomenon and has been linked to traumatic birth experiences and PTSD. In our study, we investigated how often women experience disrespect and abuse during labour and birth in the Netherlands and what proportion of these experiences was found to be upsetting. We also looked at risk factors for experiencing upsetting disrespect and abuse and to what extent upsetting disrespect and abuse influences the overall labour and birth experience. We conducted an online survey, with 12,239 respondents included in the analysis. We found a large variation in how frequently certain types of disrespect and abuse were considered upsetting, with 36.3% of women experiencing at least one situation of disrespect and abuse as upsetting. More subtle forms of disrespect and abuse, such as lack of choice, communication or support, were most prevalent and often considered upsetting. Giving birth for the first time and having a migrant background were risk factors for experiencing upsetting disrespect and abuse. Upsetting disrespect and abuse was found to have a strong impact on the overall labour and birth experience; with every additional experienced category of upsetting disrespect and abuse, the number of (very) positive labour and birth experiences decreases and the number of very negative ones increases. Although disrespect and abuse is a complex issue and its measurement subjective, this study shows that there is still a long way to go before achieving optimal respectful maternity care for all women, even in high income countries.